The case of the volcano mystery - Thompson, Carol (Scholastic New York, 1997)
Three marshmallow-mining prospectors have been scared away from their mine by a claim-jumping, snowball-throwing monster. In a wild volcanic wilderness like Jelly Jungle, what kind of monster can the twins be up against?